Endolysins: a new antimicrobial agent against antimicrobial resistance. Strategies and opportunities in overcoming the challenges of endolysins against Gram-negative bacteria - Khan, Fazal Mehmood; Rasheed, Fazal; Yang, Yunlan; Liu, Bin; Zhang, Rui (Frontiers in Pharmacology, 2024)
Antibiotic-resistant bacteria are rapidly emerging, and the increasing prevalence of multidrug-resistant (MDR) Acinetobacter baumannii poses a severe threat to humans and healthcare organizations, due to the lack of innovative antibacterial drugs. Endolysins, which are peptidoglycan hydrolases encoded by a bacteriophage, are a promising new family of antimicrobials. Endolysins have been demonstrated as an effective therapeutic agent against bacterial infections of A. baumannii and many other Gram-positive and Gram-negative bacteria. Endolysin research has progressed from basic in vitro characterization to sophisticated protein engineering methodologies, including advanced preclinical and clinical testing. Endolysin are therapeutic agent that shows antimicrobial properties against bacterial infections caused by drug-resistant Gram-negative bacteria, there are still barriers to their implementation in clinical settings, such as safety concerns with outer membrane permeabilizers (OMP) use, low efficiency against stationary phase bacteria, and stability issues. The application of protein engineering and formulation techniques to improve enzyme stability, as well as combination therapy with other types of antibacterial drugs to optimize their medicinal value, have been reviewed as well. In this review, we summarize the clinical development of endolysin and its challenges and approaches for bringing endolysin therapies to the clinic. This review also discusses the different applications of endolysins. Keywords: Antimicrobial resistance, Antimicrobial agent, A. baumannii, Gram-negative bacteria, Endolysin.